(untitled) - Carey, Francis A. (Boston, 2006)
From its first edition through this, its sixth,Organic Chemistry has been designed to meet the needs of the "mainstream," two-semester, undergraduate organic chemistry course. This best-selling text gives students a solid understanding of organic chemistry by stressing how fundamental reaction mechanisms function and how reactions occur. With the addition of handwritten solutions, new cutting-edge molecular illustrations, updated spectroscopy coverage, seamless integration of molecular modeling exercises, and state-of-the-art multimedia tools, the 6th edition of Organic Chemistry clearly offers the most up-to-date approach to the study of organic chemistry.
Hóa hữu cơ 2,Hóa hữu cơ 1
Keywords: Chemistry,organic